mitoLEAF: mitochondrial DNA Lineage, Evolution, Annotation Framework - Huber, Nicole; Hurmer, Noah; Dür, Arne; Parson, Walther (NAR genomics and bioinformatics, 2025)
The study of mitochondrial DNA (mtDNA) provides invaluable insights into genetic variation, human evolution, and disease mechanisms. However, maintaining a consistent and reliable classification system requires continuous updates. Since Phylotree updates ended in 2016, the accumulation of new haplogroup findings in individual studies has highlighted the critical need for a centralized resource to ensure consistent classifications. To address this gap, we present mitoLEAF, a collaborative, freely accessible, and academically driven repository for mitochondrial phylogenetic analyses. Unlike commercial alternatives that restrict access to their customers through subscription or purchase, mitoLEAF is openly accessible and replicable, ensuring transparency and scientific reproducibility. Hosted as a GitHub repository and supported by an interactive website, mitoLEAF provides an evolving, quality-controlled phylogenetic resource derived from GenBank, EMPOP, and peer-reviewed literature. In this first release, it expands the haplogroup landscape from 5435 to 6409 haplogroups, integrating recent findings and improving phylogenetic accuracy. By excluding known pathogenic variants, mitoLEAF aims to mitigate ethical concerns associated with reporting medically relevant variants. By prioritizing open science over commercial interests, mitoLEAF serves as a vital, community-driven platform for mitochondrial research, fostering collaboration and continuous development.